Relentlessly plain: seventh millennium ceramics at Tell Sabi Abyad, Syria - As, Bram van (Oxbow Books, Limited, 2018)
Cover -- Book Title -- Copyright -- Dedication -- Contents -- List of Contributors -- Acknowledgments -- Chapter 1: The emergence of pottery in Upper Mesopotamia: Olivier Nieuwenhuyse -- 1.1. Introduction -- 1.2. The adoption of pottery -- 1.3. The development of a mass product -- 1.4. Pottery for storage -- 1.5. Pots for cooking -- 1.6. The role of style -- 1.7. About this book -- Chapter 2: The excavations at Tell Sabi Abyad: Olivier Nieuwenhuyse -- 2.1. Introduction -- 2.2. The stratigraphy of Operation III -- 2.3. The Operation III prehistoric building sequence -- 2.4. The contextual composition of Operation III -- 2.5. The excavations at Operations IV and V -- Chapter 3: Analytical procedures: Olivier Nieuwenhuyse -- 3.1. Introduction -- 3.2. The way of the sherds -- 3.3. How much pottery? -- 3.4. Measuring fragmentation -- 3.5. Defining pottery wares -- 3.6. Reconstructing vessel shape -- 3.7. Estimating vessel volume -- 3.8. Deconstructing decoration -- Chapter 4: Analysing the prehistoric ceramic wares: Olivier Nieuwenhuyse -- 4.1. Introduction -- 4.2. Standard Ware -- 4.3. Early Mineral Ware -- 4.4. Fine Mineral Tempered Ware -- 4.5. Grey-Black Ware -- 4.6. Mineral Coarse Ware -- 4.7. Dark-Faced Burnished Ware -- 4.8. Fine Painted Ware -- 4.9. Orange Fine Ware -- 4.10. Standard Fine Ware -- 4.11. Halaf Fine Ware -- 4.12. Late Bronze Age pottery -- Catalogue -- Chapter 5: Raw materials for early ceramic production at Tell Sabi Abyad: Bonnie Nilhamn, Loe Jacobs and Bram van As -- 5.1. Introduction -- 5.2. The microscopic fabric analysis -- 5.3. The thin-section analysis -- 5.4. Discussion and conclusions -- Chapter 6: Plastered ceramics at Tell Sabi Abyad: Olivier Nieuwenhuyse and Ewout Koek -- 6.1. Introduction -- 6.2. Plastered Late Neolithic ceramics -- 6.3. The typology of plastered Standard Ware -- 6.4. Analysing the raw materials.